ANALISIS YURIDIS TERHADAP SISTEM 6 PILAR PT MELIA SEHAT SEJAHTERA SUMENEP BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Ali Banun Kalim, Moh; Mardika Alam, Suluh; Syafi’i, Imam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the legal conformity of the 6-Pillar System implemented by PT Melia Sehat Sejahtera in Sumenep Regency against the provisions of Law No. 8 of 1999 regarding Consumer Protection. The research adopts an empirical legal approach, combining normative legal analysis with field observations and in-depth interviews with members, consumers, and network leaders. The findings indicate that members hold a dual status as both consumers and business actors, entitling them to legal protection while also imposing corresponding obligations. From the six pillars analyzed, only one pillar concerning product distribution fully conforms to statutory requirements. The remaining five pillars show significant gaps between corporate claims and actual practice, particularly regarding information completeness, transparency, accessibility of support services, and product return mechanisms. Marketing presentations tend to emphasize potential income without balanced explanation of risks, which may violate the consumer’s right to accurate, clear, and honest information under Article 4 and Article 7 of Law No. 8 of 1999. It is concluded that formal legality and written policies alone are insufficient; protection must be measured by the quality of information actually conveyed and the fairness of practices experienced by consumers in the field.